Pengaruh Interpersonal Communication Dan Intrapersonal Communication Pada Employee Work Effectiveness Pada Pt Cahaya Bintang Sejati - Muyasaroh, Muyasaroh; Mahisa, Anisatul; Zaenudin, Zaenudin; Rizal, Rizmi Samsul (STAI La Tansa Mashiro, 2023)
The purpose of this research is to find out how much influence interpersonal communication and intrapersonal communication have on PT Cahaya Bintang Sejati. This research method is a quantitative type. The population in this study was 124 and the sample in this study was 90 respondents using a arandom sampling technique. The analysis technique uses a partial significance test (T test) and simultanneous (F test). Parsial test result (T) interpersonal communication variabel have a positive and significant effect on employee work effectiveness, Intrapersonal communication variabel have a positive and significant effect on employee work effekctiveness. Test result (F) interpersonal communication and employee work effectiveness variables can be said that all independent variables jointly influence significant effect on employee. Keywords: Interpersonal Communication, Intrapersonal Communication, Employee Work Effectiveness